Public Sorrows and Private Pleasures - Earle, William (Indiana University Press, 1976)
The last decade has seen the reanimation with violence and vitriol of some of the oldest errors of political thought. Perhaps their common spirit is an enthusiasm for shallow and abstract principles along with an accompanying impatience to act now at all costs. Professor Earle has grouped some of these abstractions under the title "Public Sorrows: Ideology"; they include radicalism, the absolute authority of personal conscience, pacifism, the reduction of philosophy to expertise, and the absurd celebration of civilization. He asks whether it is not time to re-open discussion of these stages of the mind, and he invites the reader to reflect on the paradoxes, ironies, and dialectical complexities of social reality. A second part, entitled "Private Pleasures: Philosophy," looks into the mystical, transcendental life of the self in its first-person singularity. If that singularity must experience a certain defeat confronted with a nature whose character is for us hypothetical, this second section looks into a region where the spirit need not be humiliated or alienated: into art, surrealism, subjectivity, and autobiography-domains more valuable because they are closer to home and to the mind's final destiny. This book is not directed solely to philosophers, but will interest the thoughtful layman as well.